2015
DOI: 10.15406/jdvar.2015.02.00031
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Cryptosporidium parvum in Dairy Calves and the Influence of Management Practices

Abstract: The occurrence of Cryptosporidium parvum in dairy calves and the influence of management practices Volume 2 Issue 2-2015

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(47 reference statements)
0
1
0
1
Order By: Relevance
“…Em alojamentos coletivos e com aglomeração, o contato entre animais é maior com consequente maior chance de infecção. Couto et al (2015) reportaram que apenas 8,5% de bezerros criados em alojamentos individuais e com comedouros e bebedouros altos apresentaram oocistos nas fezes comparado aos 21,9% de bezerros alojados em baias coletivas e com comedouros e bebedouros baixos. Animais com diarreia representam outro fator de risco para a disseminação do Cryptosporidium.…”
Section: Fatores De Risco Associados a Ocorrência De Criptosporidiose...unclassified
“…Em alojamentos coletivos e com aglomeração, o contato entre animais é maior com consequente maior chance de infecção. Couto et al (2015) reportaram que apenas 8,5% de bezerros criados em alojamentos individuais e com comedouros e bebedouros altos apresentaram oocistos nas fezes comparado aos 21,9% de bezerros alojados em baias coletivas e com comedouros e bebedouros baixos. Animais com diarreia representam outro fator de risco para a disseminação do Cryptosporidium.…”
Section: Fatores De Risco Associados a Ocorrência De Criptosporidiose...unclassified
“…In collective buildings, the contact among animals is higher, resulting in a greater probability of infection. Couto et al (2015) reported that only 8.5% of calves reared in individual pens, with high feeders and drinkers, showed oocytes in their feces, compared to the 21.9% of calves reared in collective pens, with low feeders and drinkers, showing oocytes in their feces. Animals with diarrhea contribute to the dissemination of Cryptosporidium in the environment, as mentioned by Toledo et al (2017) and Cruvinel et al (2020).…”
Section: Risk Factors Associated With the Occurrence Of Bovine Crypto...mentioning
confidence: 99%